2019
DOI: 10.1186/s12936-018-2628-3
|View full text |Cite
|
Sign up to set email alerts
|

Development of an agent-based model to assess the impact of substandard and falsified anti-malarials: Uganda case study

Abstract: BackgroundGlobal efforts to address the burden of malaria have stagnated in recent years with malaria cases beginning to rise. Substandard and falsified anti-malarial treatments contribute to this stagnation. Poor quality anti-malarials directly affect health outcomes by increasing malaria morbidity and mortality, as well as threaten the effectiveness of treatment by contributing to artemisinin resistance. Research to assess the scope and impact of poor quality anti-malarials is essential to raise awareness an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(43 citation statements)
references
References 49 publications
1
41
0
1
Order By: Relevance
“…Because data on substandard and falsified medicines, care-seeking, and costs for malaria in LMICs are limited, we performed extensive literature searches and analysis of the most recent quality data for our inputs. Epidemiological data and cost inputs were probabilistically ranged to account for uncertainty in outcomes [26]. In addition, our data analysis was limited by data availability across countries where combined indicators were only available for 51 to 63 countries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because data on substandard and falsified medicines, care-seeking, and costs for malaria in LMICs are limited, we performed extensive literature searches and analysis of the most recent quality data for our inputs. Epidemiological data and cost inputs were probabilistically ranged to account for uncertainty in outcomes [26]. In addition, our data analysis was limited by data availability across countries where combined indicators were only available for 51 to 63 countries.…”
Section: Discussionmentioning
confidence: 99%
“…disease [26][27][28]. With quality-assured medicines, beneficiaries may be cured of illness, and may even avert disability or death [26][27][28].…”
Section: Plos Onementioning
confidence: 99%
“…A review of modelling studies show that poor-quality medicines can result in serious harm and large inefficiencies which can be pitfalls to UHC, as shown in Tables 1 and 3 [15,[17][18][19][20][21][22]. The estimated economic losess from SF anti-malarials alone constitute a significant portion of the national budget for impacted countries (Table 1).…”
Section: Poor-quality Medicines: Counting the Costmentioning
confidence: 99%
“…The Substandard and Falsified Antimalarial Research Impact (SAFARI) model was developed to estimate the health and economic impact of substandard and falsified antimalarials among children under five by simulating population characteristics, malaria incidence, patient care-seeking, disease progression, treatment outcomes, and associated costs [19,20,22]. The SAFARI model is an agent-based model implemented in Python.…”
Section: Agent-based Model Simulationmentioning
confidence: 99%
“…Previous analyses across Sub-Saharan Africa found that deaths due to substandard and falsified antimalarials comprise between 3.8 and 8.9% of malaria deaths relating to cases seeking treatment [18]. Country level analyses have demonstrated that substandard and falsified antimalarials contribute substantially to the pediatric malaria burden in both Nigeria and Uganda [19,20]. While existing literature on antimalarials in Zambia emphasizes the cost-effectiveness of treating malaria with ACTs [21], to the best of our knowledge no study has yet examined the economic impact of substandard and falsified antimalarials in Zambia.…”
Section: Introductionmentioning
confidence: 99%